Kurt Vonnegut's Slaughterhouse-Five - Krouželová, Jana (Univerzita Pardubice, 2014)
The aim of this bachelor thesis is to present Kurt Vonnegut’s novel Slaughterhouse-Five in connection with the historical and literary context. First, the influence of American society and postmodernism is depicted. Second, the American war novel is defined as a genre, followed by presenting crucial themes in Slaughterhouse-Five. Autobiographic elements, the form of narration, the use of sci-fi genre and representation of war and death, the language and intertextuality are analysed. The final part of the bachelor thesis focuses on the discrepancies of Vonnegut’s fictive description of the air raid on Dresden and the commonly accepted historical facts.
Kurt Vonnegut - Jatka č.5
Keywords: Slaughterhouse-five; American war novels; postmodernism; World War II.; Jatka č. 5; americké válečné romány; postmodernismus; druhá světová válka